The 981C>T polymorphism in protein tyrosine phosphatase 1B is associated with decreased risk of coronary artery disease in Chinese Han population - Zhou, Xiang; Xu, Weiting; Chen, Jianchang (Atherosclerosis, 2011)
The present study was designed to investigate the potential association between the 981C>T polymorphism in protein tyrosine phosphatase 1B (PTP-1B) and coronary artery disease (CAD). We conducted a hospital-based case–control study with 864 CAD patients and 1008 controls to explore the association between the PTP-1B 981C>T polymorphism and risk of CAD in Chinese Han population. Subjects with the variant genotypes (CT+TT) had a 52% decreased risk of CAD relative to CC carriers (adjusted odds ratio, 0.48; 95% confidence interval, 0.39–0.60). The 981C>T polymorphism was associated with a higher body mass index and serum triglyceride levels in both CAD patients and controls. Moreover, this polymorphism was found to be associated with a lower serum glucose levels in cases, but not in controls. Our study demonstrates that the PTP-1B 981C>T polymorphism is associated with decreased risk of CAD in Chinese Han population.